Understanding the public sector pay gap - Maria M. Campos; Domenico Depalo; Evangelia Papapetrou; Javier J. Pérez; Roberto Ramos (IZA Journal of Labor Policy, 2017)
We uncover the short- and long-run structural determinants of the existing cross-country heterogeneity in public-private pay differentials for a broad set of OECD countries. We explore micro data (EU-SILC, 2004-2012) and macro data (1970-2014). Three results stand out. First, when looking at pay gaps based on individual data, more than half of the cross-sectional variation of the sample can be accounted for by the degree of exposure to international competition, as well as by the size of the public sector labor force and its composition (i.e., the intensity in the provision of pure public goods), while labor market institutions play a very limited role. Second, we find that in some countries, pay gaps have narrowed down significantly during the recent financial crisis, this decrease being explained by the widespread process of fiscal consolidation rather than by changes in the previous factors. Third, we show that in the log run, openness to international trade and improvements in the institutional quality of governments are associated with decreases in the public-private wage gap. Our findings can be rationalized by a body of research stressing noncompetitive wage settlements in the public sector.
Keywords: J31; J45; H50; 330; Public sector pay gap; Government monopolistic power; Wage-setting institutions